Effect of Biogas Slurry on the Nutrient Cycling and Micro-organisms Community in Two Types of Soil - Pengcheng Li; Dongqi Jiang; Shuqiang Wang; Xianying Zhang; Yulan Zhang; Yonghuan Wang; Zhenhua Chen; Nan Jiang (BioResources)
The biogas slurry (BS) generated through the anaerobic fermentation of biogas in pig farms is extensively employed as an organic fertilizer in Northeast China. BS is often used in large amounts because of fragmented farmland ownership resulting from previous local policies. In this work, 20 m3 · 667m-2 of BS was applied to black soil twice and to aeolian sandy soil once to explore microbial-driven nutrient cycling. The results indicated that BS increased organic carbon, total nitrogen, and total phosphorus contents in black soil. The activities of C-cycling and P-cycling enzymes in black soil were enhanced, while the activities of P-cycling enzymes in aeolian sandy soil were reduced. The BS application increased the abundance ratio of fungi to bacteria in both soil types. Total carbon, total nitrogen, and total phosphorus primarily influenced the microbial community structure in black soil, while pH was the key factor in aeolian sandy soil. However, the excessive increase of heavy metals in black soil treated twice BS posed a potential risk to the environment. Utilizing BS as fertilizer is a viable strategy applicable for Northeastern China’s agriculture, and application dosages must be adjusted according to experimental results.